STRUKTUR KALIMAT DALAM BAHASA ARAB: TINJAUAN TEORITIS TERHADAP MUBTADA DAN KHABAR - Syaira Balqis Ananda Astia; Ilfina Muttaqwiyatul Qudsiyyah; Ridha Shafa Athaya (Jurnal Sathar, 2025)
This study aims to theoretically examine the sentence structure in Arabic, especially the elements of mubtada and khabar as core components in the number of ismiyyah (nominal sentences). In Arabic grammar, nominal sentences have their own uniqueness because they do not require verbs to convey information. Therefore, understanding the position and function of mubtada and khabar is very crucial for learners and researchers in the fields of Arabic linguistics, tafsir, and Islamic studies. This study uses a qualitative approach of the literature type by examining classical works such as Al-Kitāb by Sibawayh, Mughni al-Labīb by Ibn Hisham, and Al-Kashshāf by Az-Zamakhshari. The study is also strengthened by modern references to bridge theory with contemporary learning needs. The results of the study show that mubtada is generally in the form of isim ma'rifah known by the interlocutor, while khabar functions to complete the meaning with various forms such as mufrad, jumlah, and syibh jumlah. This study also highlights the phenomenon of taqdim wa ta’khir (reversal of order) used in rhetorical contexts. Understanding the mubtada-khabar structure has proven to be important in reading classical Arabic texts, including the Qur’an. Thus, this study contributes to enriching theoretical and applied understanding of Arabic syntax.